ENHANCING EFL SPEAKING SKILLS THROUGH COMMUNICATIVE AND INTERCULTURAL INSTRUCTION IN THAILAND - Taufiqur Rahman; Edi Yulianto (International Journal of Community Service in Language, Literature, Culture, and Their Teaching, 2026)
This community service article reports on an International Community Service (International Community Service) program conducted at Chongraksat Wittaya School, Pattani, Thailand. The program addressed students limited English proficiency, low confidence in speaking, and minimal exposure to communicative English learning. Preliminary observations revealed that English instruction was dominated by the use of the mother tongue, resulting in passive classroom interaction and low student motivation. To address these issues, a Fun Learning approach was implemented, focusing on games, interactive activities, and oral practice to create an enjoyable and supportive learning environment. The program also introduced basic Indonesian language and cultural knowledge to promote intercultural understanding. The activities were conducted from July to September 2025, involving Mathayom (Junior and Senior high school) students through 74 teaching sessions. The results indicate improvements in student vocabulary mastery, pronunciation, speaking confidence, and classroom participation. Additionally, students demonstrated increased awareness of Indonesian culture and basic Indonesian expressions. This program shows that Fun Learning is an effective method for enhancing student English communication skills while simultaneously fostering cultural exchange in an international educational setting.